Using instructional games in an open and distance learning environment / Anealka Aziz Hussin …[et al.] - Aziz Hussin, Anealka; Anuar, Mazura; Jauhari, Nadiah Thanthawi; Dass, Laura Christ; Syed Ahmad, Tuan Sarifah Aini (Universiti Teknologi MARA, 2021)
Learning in an open and distance learning mode is challenging, especially to make students participate actively during the learning session. Students prefer to 'hide' by switching off the camera and microphone on their laptops throughout the learning session. Even during activity time, regular students will be responding, and many prefer to be present silently. Getting students to engage actively is a challenge for the instructors. They need to plan the lessons and activities creatively to motivate them to learn and eventually participate in the lessons. One of the approaches to teaching and learning that has been proven to increase students' motivation and engagement is by integrating gamification elements in the learning process. This approach has led to the creation and development of various games to suit various needs in education. FunLinguistics is a linguistics game for students taking language and Linguistics course. The purpose of the creation of this game is to help students doing their revision for tests. The game covers topics like morphology, syntax, semantics, and pragmatics. This paper intends to describe the process of developing the game and share students' view regarding the approach used to assist them in revising for tests. A structural gamification approach using Microsoft PowerPoint as the main platform with Visual Basic Applications (VBA) was adopted. The game consisted of questions set at different difficulty levels based on Bloom's Taxonomy. An online survey was conducted to get feedback on using the game for revision purposes. This paper hopes to offer some ideas for other language instructors to adopt and try out with their students.